A alfabetização científica e o desenvolvimento de situações desencadeadoras de aprendizagem: sobre a importância ecológica do uso da água - Santos, Alessandro Cardoso (Universidade Federal de São Carlos, 2024)
This dissertation presents a qualitative study employing descriptive and interpretive approaches through the analysis of students' discourse. The research question guiding this study is: How do elementary school students participate in natural science activities within a learning-triggering situation aimed at scientific literacy? The objective is to analyze students' statements for indications of conceptual elements regarding the ecological use of water. The focus of the analysis lies in the students' interactions during a study activity, framed within a conceptual teaching proposal for the process of scientific literacy, involving hypothesis generation and problem-solving through local newspaper reports on water scarcity. The study aims to describe and interpret students' interactions in study activities, particularly during analytical debates and conceptual synthesis proposed in the Learning-Triggering Situation (LTS). Students' statements were analyzed to identify conceptual elements related to the ecological use of water and its historical importance during participation in a teaching activity designed to foster synthesis within the individual-group-class relational dynamic. Data for this study were collected during a pedagogical intervention involving thirty fifth-grade students at a public school in Campinas, São Paulo, in 2024. Classroom sessions were recorded in audio and video formats,transcribed, and analyzed using the theoretical framework of Cultural-Historical Theory, with an emphasis on conceptual teaching. The data analysis was grounded in the hypothesis that the pedagogical approach to science teaching, framed within an Everyday-Emerging Situation, prompted intentional expressions from students. These expressions indicated a conceptual synthesis and relationships between the specific problem presented in the activity—particularly issues related to water usage—and the general ecological concept, connecting to fundamental scientific concepts of ecology regarding water as a resource. As part of the outcomes of this research, an educational product was developed, synthesizing the actions of the Teaching-Guided Activity for the implementation of the Learning Trigger Situation conducted in the study.
Scientific literacy and the development of learning-triggering situations: on the ecological importance of water use
Keywords: Alfabetização científica; Ensino conceitual; Situação desencadeadora de aprendizagem; Uso ecológico da água; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM